2019
DOI: 10.1155/2019/3075840
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Open Defecation in the Wa Municipality of Ghana: Empirical Findings Highlighting Sociocultural and Economic Dynamics among Households

Abstract: This study examined sociocultural and economic factors determining open defecation in the Wa Municipality, Ghana. The study employed a mixed method approach involving questionnaire administration to 367 households systematically selected from 21 communities, observation, and eight key informant interviews. The mixed logit model was used to determine the factors that significantly influence open defecation. The findings revealed that 49.8% of households had no form of toilet facility at home and were either usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
87
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(133 citation statements)
references
References 9 publications
16
87
2
2
Order By: Relevance
“…Osumanu et al [30] have confirmed that open defecation leads to large disparities between rich and poor. Senyk [31] has reported that in countries like India, sewage treatment is done only by the lowest caste.…”
Section: Impact Of Open Defecation On Sdg 10mentioning
confidence: 94%
“…Osumanu et al [30] have confirmed that open defecation leads to large disparities between rich and poor. Senyk [31] has reported that in countries like India, sewage treatment is done only by the lowest caste.…”
Section: Impact Of Open Defecation On Sdg 10mentioning
confidence: 94%
“…A study of open defecation in Ghana revealed that the lack of toilets at home affected the decision of open defecation. 38 Thus, it is necessary to adopt the suggestion related to the location of toilet facility on premises, taking into account the local environment. In addition, a study conducted in Addis Ababa in 2017 provided another important implications on the location of toilets, with a contrary finding such that proximity of sanitation facilities within 15 meters of homes increased acute diarrhea compared to facilities located more than 15 meters away.…”
Section: Factors Of Diarrhea Of Malawian Children Under Fivementioning
confidence: 99%
“…The fact that traditional norms have been suggested to influence OD has been reported in previous studies. A similar study conducted in Northern Ghana found 57% of adults acknowledge that OD was an 'age long practice" compared to other reasons such as financial constraints (18.6%) and bad condition of public toilets (8.4%) [33]. Unlike the case of Osumanu et al's study which focused on adults, this study was conducted among the school aged children.…”
Section: The Influence Of Culture On Open Defaecation Practicementioning
confidence: 88%
“…The case of taboo being associated with OD behaviour in this study was unexpected and cannot be explained as it did not come out as a major cultural factor during the reconnaissance visits and the FGDs. Nevertheless, other studies have found men to refuse to stop open defaecation because of toilet-associated taboos with in-laws and female grown-up children [33].…”
Section: The Influence Of Culture On Open Defaecation Practicementioning
confidence: 97%